Power, dominance and homosocial solidarity in young men’s cyber talk - Azianura Hani Shaari,; Shahrul Nazmi Sannusi, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Men and women speak differently as their linguistic behavior reflects their gender identity and signifies their position in the society. This article discusses the conversational style of men in the online communication environment, using the Kiesling’s framework of men’s language. A documentation of naturally occurring conversations on Facebook was made over a 12-month period whereby data is categorized and analysed using Content Analysis, WordSmith Tools 5.0 and MS Word Advanced Find Function. Purposive sampling was employed in selecting the participants. The sample consisted of 60 males and 60 females to allow for comparison. Language produced by the male participants, however, remained as the central issue of the analysis as well as discussion. If Kiesling’s framework discusses men’s language from the western sociocultural perspectives, findings of the present research indicated a list of variables of men’s discourse in the specific context of the Malaysian online communication environment. Apart from that, the findings have demonstrated some culturally-embedded elements of power, dominance, and homosocial solidarity as well as a strong use of masculine speech forms in this specific context of male’s interaction. Finally, the findings have also suggested some significant aspects of men’s discourse in the specific context of the Malaysian online communication environment.